Critical Thinking Skills in Rotational Dynamics: Learning Physics With and Without Free-body Diagrams - Ogi Danika Pranata; Noperma Noperma (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2023)
This quasi-experimental study investigates the impact of using free-body diagrams on the critical thinking skills of students studying rotational dynamics at MAN 1 Sungai Penuh. The study involved 140 eleventh-grade students, divided into an experimental group and a control group, each consisting of 70 students. The experimental group received instruction using free-body diagrams, while the control group followed traditional teaching methods. Critical thinking skills were assessed using a test comprising five essay questions, each representing different aspects of critical thinking: likelihood and uncertainty analysis, problem solving and decision making, reasoning, hypothesis testing, and argument analysis. Descriptive statistics and independent samples t-tests were employed to analyze the data. The results revealed that the experimental group outperformed the control group in all aspects of critical thinking skills, with statistically significant differences and strong effect sizes. Specifically, the experimental group showed notable improvements in argument analysis, reasoning, and hypothesis testing. The findings suggest that the use of free-body diagrams significantly enhances students' critical thinking skills in the context of rotational dynamics. This study underscores the importance of incorporating visual learning aids in physics education to foster deeper understanding and improve analytical skills. The results have important implications for teaching practices, advocating for the integration of free-body diagrams to develop students' higher-order thinking skills effectively